PAQR9 regulates hepatic ketogenesis and fatty acid oxidation during fasting by modulating protein stability of PPARα - Yijun Lin; Lingling Chen; Xue You; Zixuan Li; Chenchen Li; Yan Chen (Elsevier, 2021)
Background: The cycle of feeding and fasting is fundamental to life and closely coordinated with changes of metabolic programs. During extended starvation, ketogenesis coupled with fatty acid oxidation in the liver supplies ketone bodies to extrahepatic tissues as the major form of fuel. In this study, we demonstrated that PAQR9, a member of the progesterone and adipoQ receptor family, has a regulatory role on hepatic ketogenesis. Methods: We analyzed the phenotype of Paqr9-deleted mice. We also used biochemical methods to investigate the interaction of PAQR9 with PPARα and HUWE1, an E3 ubiquitin ligase. Results: The expression of Paqr9 was decreased during fasting partly depending on PPARγ. The overall phenotype of the mice was not altered by Paqr9 deletion under normal chow feeding. However, fasting-induced ketogenesis and fatty acid oxidation were attenuated by Paqr9 deletion. Mechanistically, Paqr9 deletion decreased protein stability of PPARα via enhancing its poly-ubiquitination. PAQR9 competed with HUWE1 for interaction with PPARα, thus preventing ubiquitin-mediated degradation of PPARα. Conclusion: Our study reveals that PAQR9 impacts starvation-mediated metabolic changes in the liver via post-translational regulation of PPARα.